(untitled) (Nepalese Journal of Management Research, 2021)
Human capital is an important asset for any organization. Physical and capital resource can be mobilized properly through human resources. Physical and capital resources by themselves cannot improve efficiency or contribute to increased rate of return on investment. The efficiency of capital and physical resource can be achieved through combined efforts of human resources. This paper is descriptive design. The study tackled areas of workforce diversity effects on diversity of performance of employees and how workforce diversity can be managed to the positive outcomes of an organization. Workforce diversity is combination of different caste, gender, age, attitude, religion, ability, skills, region, perception, race, sex, experience and cultural differences. It is the differences and similarities between the employees of any organization. It is the process of bringing verity of people in the same workplace. Effective management of diversity recognizes that people from different backgrounds, culture and experience can bring new ideas to the workplace. Workforce diversity leads an organization in to creativity, innovation, able to retain talent workforce, energize people and boosts them and reduced grievances. Workforce diversity promotes creativity, innovative problem solving, productivity and increase cultural diversity, increase in enterepreneural behavior and values within employees. Diversity management emphasizes on building specific skills, creating policies and drafting practices that get the best from every workers. So, diversified workforce provides various advantages to organization (i.e. creativity, change adoption, problem solving, new thinking and thought, flexible adoption to organizational change and beliefs). The study reveals that there is a positive correlation between good workforce diversity and organizational change.